10 Years of Academicus International Scientific Journal - The story of contribution in the research in 20 Issues. - Maria Immacolata Macioti (Academicus, 2019)
A delightful scientific journal which, since its birth in Albania, has quickly learned the ways of the world, bringing Balkan matters and issues abroad, to the East as well as to the West, but also conversely, making known in the Land of Eagles which were the main topics of reflection and study, such as the problems of distant countries and other cultures.